INFLUENCE OF WELDING TECHNIQUES ON MICROSTRUCTURE AND HARDNESS OF STEEL JOINTS USED IN AUTOMOTIVE AIR CONDITIONERS (Metallurgy and Foundry Engineering, 2018)
Austenitic steels belong to a group of special-purpose steels that are widely used in highly aggressive environments due to their enhanced anticorrosive behavior and high mechanical properties. The good formability and weldability of these materials has made them very popular in automotive AC systems. This study presents the results of hardness tests and microstructure observations on plasma- and laser-welded joints. The examined joints consisted of two different stainless steel components; i.e., a nipple made from corrosion-resistant AISI 304 steel and a corrugated hose made from 316L steel. Microplasma welding was carried out on a workstation equipped with an MSP-51 plasma supply system and a BY-100T positioner. The laser-welded joint was made on a numerically controlled workstation equipped with an Nd:YAG laser (without filler material) with 1 kW of maximum power; the rotational speed of the welded component was n = 4 rpm. Microstructural observations were performed using a scanning electron microscope and an optical microscope. Vickers hardness was measured with a hardness tester. The obtained results proved that both the microplasma- and laser-welded joints were free from any visible welding imperfections. In the micro areas of the austenitic steel weld, crystals of intercellular ferrite appeared against a background of austenite. The crystallization front (depending on the welding technology) was running from the fusion line towards the weld axis. The grain size depended on the distance from the fusion line.